The Influence of Electronic Word of Mouth And Brand Image On High-End Tumble Purchase Intention - Harnadi Putra; Ridho Bramulya Ikhsan (Journal of E-business and Management Science, 2023)
The High-End Tumbler product is a premium version of a drinking cup, but the presence of competitors with low-end versions makes consumers switch because it has the same function at an affordable price. This study aimed to determine the effect of e-wom and brand image on the purchase intention of high-end tumblers, both simultaneously and partially. This type of research is quantitative, with the unit of analysis being high-end tumbler purchase intention users in DKI Jakarta. Data collection used a questionnaire distributed to 100 high-end tumbler purchase intention users in DKI Jakarta. They were testing the data using validity, reliability, classical assumption test, and multiple linear regression. The results of the study prove that all data are declared valid and reliable. In addition, all classical assumption tests are met. Multiple linear regression testing proves that e-wom and brand image affect the purchase intention of high-end tumblers, both simultaneously and partially.